ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN LABA PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN SIKKA - Lodan, Alfonsa; Soleiman, Iriany Dewi (Jurnal Riset Ilmu Akuntansi, 2023)
The study aims to analyze the influencing factors changes in profits of the Regional drinking Water Company (PDAM) of  Sikka Regency.The factors studied are ROA (Return On Assets),BOPO (Operating Costs to Operating Income),and TATO (Total Assets Turnover).The population used in this study is the Financial Report of Regional Drinking Water Company (PDAM) in Sikka Regency.The sampel used is the Report on Change in Profit and Loss of the Regional Drinking Water Company (PDAM) in Sikka Regency for 2019 to 2021.A useful analytical technique is multiple linear regression with a 5% confidencelevel.Hipothesis testing uses t-statistics to test the effect partially and f-statistics to test effect simultaneously (together) whivh is tested using SPPS Version for windows.Based on the results of data analysis,it shows:1)ROA (Return On Assets)partially has a positive effect on profit changes with a t-count of 6.156 with a significance level of 0.007 less than 0.05,so the calculated table is (6.156 larger than 2.03693).2)BOPO (Operating Costs to Operating Income) partially has a positive effect on changes in profit with a t-count of 11.679 with a significance level of 0.000 less than 0.05,the table is calculated (11.679 larger than 2.03693).3) TATO (Total Assets Tunover) partially has a positive effect on changes in profit with a t-count of 6.485 with a significance level of 0.001 less than 0.05 the table is calculated (6.485 larger than 2.03693).